The Influence Of Job Satisfaction And Job Stress Work On Turnover Intention In CV. Zharry Home Creative - Putri, Deva Nadia; Lestari, Suci Putri; Rahwana, Kusuma Agdhi (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study is to determine the effect of Job Satisfaction and Job Stress on Turnover Intention in Employees of CV. Zharry Home Creative. The method used in this study is a quantitative approach with a sample of 60 respondents from employees of CV. Zharry Home Creative. The data used in this study are primary data and secondary data. The analytical tool used in this study was multiple regression analysis using SPSS version 25. The results showed that simultaneously job satisfaction and work stress have a significant effect on turnover intention. Partially, job satisfaction has a significant effect on turnover intention. Partially, work stress has a significant effect on turnover intention.